Extracellular polymeric substances from marine actinobacterium of Micromonospora sp. and their antioxidant activity - Rinki Susan George; Pitchiah Sivaperumal; Anitha Roy (Wolters Kluwer Medknow Publications, 2022)
Actinobacteria, Gram-positive bacteria are the largest phyla among the major species in the bacteria domain. Micromonospora sp. is one of the secondary metabolite-producing Actinobacteria, and it has a comprehensive spectrum of antibacterial, antifungal, antitumor, antiviral, antiparasitic, diabetogenic anti-inflammatory, insecticidal, inhibitory of enzyme, antioxidant, and other biological activities. The objective of the study is to assess the antioxidant activity of the Actinobacterium Micromonospora sp. producing extracellular polymeric substances (EPSs). Enumeration and isolation of Actinobacteria from sediment samples are done. The marine Actinobacteria, Micromonospora sp. are identified by melanoid pigments and other chemotaxonomical characteristics. EPS is produced from the potential marine Actinobacteria and their components are estimated. The total antioxidant value is found for the EPS. The antioxidant activity of the ascorbic acid equivalent which was 142.65 μg/ml was equivalent to 150 μg/ml of the total antioxidant activity of the EPS produced. The role of different antioxidants and the action in different diseases were challenged since they could act as many mechanisms such as reducing power, providing hydrogen to radicals, and scavenging activity (free radical). To conclude, the potent antioxidant activity was obtained from Actinobacteria Micromonospora sp. producing extracellular substances. These extracts might bear anticancer metabolites and are considered a potent anticancer drug.